Wholegrain oat quality indicators for production of extruded snacks. (15th January 2023) - Nikinmaa, Markus; Mustonen, Sari A.; Huitula, Lauri; Laaksonen, Oskar; Linderborg, Kaisa M.; Nordlund, Emilia; Sozer, Nesli
Abstract: Extrudates made of 30 different wholegrain oat flour samples with diverse chemical composition were prepared using a twin-screw extruder (screw speed 400 rotations per minute, temperature profile 140-130-90-85 °C (die to feed), flour feed rate was 60 g/min and total moisture content 15%). Each wholegrain oat flour was mixed with 30% rice flour (dry basis) and extruded under constant temperature, screw speed, water and feed rates. Generic descriptive sensory analysis was performed for 10 selected samples. Principal component analysis (PCA) and partial least squares regression (PLS) models were used to assess interactions between the sensory and instrumental data. Degree of extrudate expansion varied between 143 and 305%, while density varied between 198 and 785 kg/m 3 . Hardness of samples were between 44 and 150 N. As expected, starch content was positively, and fat content negatively correlated with degree of expansion. Musty aroma and the perceived hardness correlated with fat content in the PLS model, while the perceived crispiness correlated with expansion. Quality indicators such as thousand seed weight (TSW), and peak viscosity showed significant correlation with expansion in both instrumental and sensory tests; therefore, they can be utilized as quick predictive measurements to assess the quality of wholegrain oat based extrudates. Highlights: Large variation in extrusion performance among the 30 oat flour samples. Starch content positively correlated with expansion and crispiness. Higher fat content negatively affected structure and texture. Sensory analysis showed fat content correlated with hardness and musty aroma. Thousand seed weight and peak viscosity potential quality indicators for oat in extrusion.